2021
DOI: 10.18388/abp.2020_5441
|View full text |Cite
|
Sign up to set email alerts
|

miR-3188 Regulates proliferation and apoptosis of granulosa cells by targeting KCNA5 in the polycystic ovary syndrome

Abstract: Abnormal proliferation of granulosa cells is implicated in ovarian dysfunction and dysregulated folliculogenesis in the polycystic ovary syndrome (PCOS). Aberrant microRNA (miRNA) expression might contribute to disordered folliculogenesis and granulosa cell proliferation in PCOS. This study aimed to investigate the roles of miR-3188 in ovarian dysfunction, as well as the mechanism involved in granulosa cell proliferation in PCOS. Firstly, peripheral blood samples were isolated from PCOS patients and healthy co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Consistent with previously published studies [10,11], our data indicates that KCNA5 is downregulated in PCOS. Additionally, compared to the controls, Hsc70 overexpression decreased KCNA5 levels, and Hsc70 knockdown increased KCNA5 expression.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Consistent with previously published studies [10,11], our data indicates that KCNA5 is downregulated in PCOS. Additionally, compared to the controls, Hsc70 overexpression decreased KCNA5 levels, and Hsc70 knockdown increased KCNA5 expression.…”
Section: Discussionsupporting
confidence: 93%
“…Importantly, Hsc70 interacts with CHIP to facilitate KCNA5 degradation in mammalian cells [8]. KCNA5 is downregulated in PCOS, and KCNA5 upregulation inhibits granulosa cell proliferation in PCOS [10,11]. However, the interplay between Hsc70 and KCNA5 in PCOS has not been reported to date.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu C et al reported that p53 deacetylation is a crucial step of miR-874-3p induce GCs apoptosis [ 12 ]. miR-3188 promoted the cell cycle by decreasing p21 in KGN cells [ 52 ]. And also, cellular stresses are activated in response to p53 signaling through HB-EGF induction [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs regulate the function of GCs by altering the expression levels of target genes. For example, in the granulosa-like tumor cell line, miR-1388 promotes cell cycle progression by increasing cyclin D1 and decreasing p21 levels by targeting potassium voltage-gated channel subfamily A member 5 ( KCNA5 ) [ 31 ]. Another study showed that miR-29c participates in the regulation of follicular atresia by inhibiting GC apoptosis by targeting SMARCA2 via the NORFA-SMAD4 axis [ 32 ].…”
Section: Introductionmentioning
confidence: 99%